Boosting adults scientific literacy with experiential learning practices - Eduardo Dopico; Alba Ardura; Yaisel J. Borrell; Laura Miralles; Eva García-Vázquez (European Journal for Research on the Education and Learning of Adults)
Working as an interdisciplinary team, from the departments of Education and Biology we organized a short experiential learning seminar followed by a hands-on workshop for the promotion of citizen scientific literacy. Participants were adult lifelong learners enrolled in University programs, and others were adults interested in scientific activities without a motivation towards continuous learning. Through a teaching dynamic based on learning science by doing science, they could make close contact with the research procedures in scientific laboratories and learn about the use of DNA to identify unknown fish species. The data collected about their learning gains in this science literacy experience showed that elder lifelong learners found the basic scientific concepts more difficult to understand than the non-lifelong learners, but were more motivated to engage in science education activities than the latter, which makes them a very interesting potential group to recruit for citizen science initiatives.